BAGI HASIL (PROFIT SHARING) SEBAGAI BENTUK PERKEMBANGAN EKONOMI ISLAM DI INDONESIA - Ernawati, Ernawati (Jurnal Muhakkamah, 2020)
The principle of profit sharing is an operational alternative that can be applied in banking activities to avoid usury by sharing in profits and losses based on Islamic sharia. In the principle of profit sharing is based on the principle of At Ta awun, which is to help each other and cooperate among community members for good and the principle of avoiding Al Iktinaz, namely holding money (funds) and leaving it idle which does not rotate in transactions that are beneficial to the general public. One of the principles of profit sharing (Syirkah) is applied in the mudharabah contract. Mudharabah consists of mudharabah mutlaqah and mudharabah muqayyadah. Profit sharing in mudharabah financing is according to the agreed ratio and is calculated based on the gross revenue (revenue sharing) from the results of the mudarib business. Because most of the funds used in mudharabah financing come from public funds (third party funds). So that Islamic banks must take measures so that funds from depositors of funds used in financing are not harmed because the risk in financing for the results is relatively high. Efforts to save problem financing are carried out by restructuring financing through rescheduling, adding financing facilities and temporary equity participation. Meanwhile, the settlement of problem financing is carried out through guarantees, write-offs and settlement of disputes both through litigation and non-litigation (arbitration).